Variasi Panjang Fragmen Gen ND3 Burung Famili Ploceidae Endemik Pulau Jawa (The Length Variation of ND3Gen Fragmen of Java’s Endemic Ploceidae Family’s Birds) - Fitria, Ana; Susanti, R (Biosaintifika: Journal of Biology & Biology Education, 2009)
Ploceidae family’s birds in Indonesia consist of 41 species include 13 species as Java’s endemic. Some species of Ploceidae family were start to rarely oberved, because of new house developing and hunting as a pets, zoo collection and education kit. It’s need some efforts to conserve these rare species through improving the habitat, rehabilitation, nursery, controlling, law inforcement for hunters, and genetic conservation according to a knowledgement of genetic variation. The research aimed to knew the length fragmen of ND3 DNAmt Gen and genetic variation among species of Ploceidae family’s birds. 11 species were observe for morphology’s characteristic than blood sample were collected for DNA isolation with Dixit methode. ND3 gen were amplificated by DNA isolated with PCR used H11151 and L10755 primer. PCR’s gain were visualized with 2 % agarose gel. The length fragmen of ND3 DNAmt were 321bp for Bondol Jawa, 338 bp for Bondol Haji and Bondol Peking, 393 bp for Burung Gereja Erasia, 413 bp for Manyar Emas, 406 bp for Gelatik Jawa, 334 bp for Manyar Tempua and Manyar Jambul, 351 bp for Pipit Benggala, 333 bp for Bondol Hijau Binglis, 317 bp for Pipit Zebra. The conclusion of this research were : 1). the length variation of ND3 DNAmt Gen among 11 species range from 317 – 413 bp and 2). morphological variation and length variation of ND3 DNAmt Gen shows that there was genetic variation among species of Ploceidae family’s birds. Key words : Ploceidae, ND3 Gen, Java’s endemic